Reflecting Pancasila in Environmental Crimes Enforcement: Diffusing Values to Indonesia’s Laws - Arief, Syamsul; Hasibuan, Fauzie Yusuf; Mulyadi, Lilik (Pancasila and Law Review, 2024)
Pancasila and the 1945 Constitution play crucial roles in shaping Indonesia's governance, societal values, and legal framework, particularly in safeguarding the right to a clean and healthy environment. However, environmental destruction persists due to inadequate corporate accountability enforcement and systemic flaws. Hence, the article examines Indonesia's regulatory approach to holding corporations accountable for environmental crimes through the lens of Pancasila. It explores how Pancasila's principles influence environmental regulations, emphasizing nature harmony, fair treatment, and social justice. Effective enforcement aligned with these principles can promote sustainable development and environmental protection. Challenges like regulatory gaps and corruption need addressing. Building an optimal framework entails integrating Pancasila values into preventive and punitive measures, ensuring transparency, community participation, and fair enforcement. Success hinges on robust legal structures and public involvement, with initiatives like corporate collaboration, transparency, and strict liability enforcement. Implementation requires the establishment of mechanisms such as an Environmental Court and community oversight for victim recovery. This article uses a normative approach elaborated through a conceptual and statute approach.